온도와 광도가 톨루엔-NOx-공기 혼합물의 광산화 반응에 미치는 영향의 비교 - 주옥정; 배귀남; 최지은; 이승복; 김영성; 문길주; 윤순창 (한국대기환경학회, 2007)
To differentiate temperature effect from the light intensity effect on the formation of secondary products duringthe photooxidation of toluene-NOx-air mixtures, steady-state air temperature was changed from 20C to 33C at thesame light intensity of 0.39min-1 in an indoor smog chamber. Smog chamber consisted of 64 blacklights and a 5.8-m3 reaction bag made of Teon lm. Air temperature was controlled by an air-conditioning system. The startingtime for rapid conversion of NO to NO2 intensity effect, the ozone formation time and the ozone production rate were insensitive to air temperature.Although the formation time for secondary organic aerosols was not changed, the particle number concentrationincreased with temperature. However, the newly formed secondary organic aerosol mass at lower temperature washigher than that at higher temperature. Since light intensity signicantly affected the starting time and quantity offormation during the photooxidation of toluene-NOx-air mixtures.